2020
DOI: 10.1080/08824096.2020.1748001
|View full text |Cite
|
Sign up to set email alerts
|

It’s a match (?): Tinder usage and attitudes toward interracial dating

Abstract: The increased popularity of dating apps such as Tinder coupled with the rise in interracial marriages form the foundation of this study which explores the role played by visual and cultural cues in people's dating decisions. Using a within-group 2*3 experimental design (N = 331) among a convenience sample of adults in the Netherlands, this study provides insight into how the ethnicity associated with profile pictures and names impact the evaluation of a potential date on Tinder. Overall, respondents ranked Cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Aside from personality traits, future research could also focus on demographic variables, such as race, ethnicity, and gender. Research has shown that ethnicity may impact the evaluation of a potential date on dating apps such as Tinder (Ranzini & Rosenbaum, 2020) and according to our findings, some ghosters decided to ghost because they thought the other person was racist, thereby suggesting that ghosting experiences may differ depending on the race or ethnicity of users. While additional quantitative analyses within the current study did not find significant gender differences in terms of ghosting others and rating the ghosting experience as painful, we did not focus on gender differences within our qualitative analyses.…”
Section: Discussionsupporting
confidence: 61%
“…Aside from personality traits, future research could also focus on demographic variables, such as race, ethnicity, and gender. Research has shown that ethnicity may impact the evaluation of a potential date on dating apps such as Tinder (Ranzini & Rosenbaum, 2020) and according to our findings, some ghosters decided to ghost because they thought the other person was racist, thereby suggesting that ghosting experiences may differ depending on the race or ethnicity of users. While additional quantitative analyses within the current study did not find significant gender differences in terms of ghosting others and rating the ghosting experience as painful, we did not focus on gender differences within our qualitative analyses.…”
Section: Discussionsupporting
confidence: 61%
“…The dating landscape does not hold equal opportunity for everyone: Some individuals have greater or fewer dating options because they belong to groups that enjoy privilege or face stigma on the dating market. For example, considerable research suggests that whiteness is privileged in the context of online dating (at least in White-majority cultures), with White targets receiving greater romantic interest than targets from other racial groups (e.g., Chopik & Johnson, 2021 ; OKCupid, 2014 ; Ranzini & Rosenbaum, 2020 ). Racial and gender stereotypes intersect in ways that may lead to particularly high levels of prejudice against Black women and Asian men (e.g., Robnett & Feliciano, 2011 ), consistent with North American stereotypes that link Black and Asian identities with masculinity and femininity, respectively ( Galinsky et al, 2013 ; Schug et al, 2015 ).…”
Section: Future Directionsmentioning
confidence: 99%
“…Digital technologies and diverse social media platforms facilitate electronic contact (or E-contact) and communications between people from different ethnic, racial, and cultural groups and improve intergroup harmony by reducing prejudice against sexual minorities (White et al, 2019(White et al, , 2021. Dating platforms, for example, create an opportunity for users to develop interracial relationships (Ranzini & Rosenbaum, 2020). However, the cross-cultural contact in the online dating context can also increase the risk of being exposed to bias, prejudice, stigma, and exclusion.…”
Section: Race-based Prejudice and Discrimination In The Digital Dating Contextmentioning
confidence: 99%